Prevalence of mild behavioral impairment in mild cognitive impairment and subjective cognitive decline, and its association with caregiver burden. (7th September 2017) - Sheikh, Faisal; Ismail, Zahinoor; Mortby, Moyra E.; Barber, Philip; Cieslak, Alicja; Fischer, Karyn; Granger, Robert; Hogan, David B.; Mackie, Aaron; Maxwell, Colleen J; Menon, Bijoy; Mueller, Patricia; et al.
ABSTRACT: Background: Mild behavioral impairment (MBI) describes later life acquired, sustained neuropsychiatric symptoms (NPS) in cognitively normal individuals or those with mild cognitive impairment (MCI), as an at-risk state for incident cognitive decline and dementia. We developed an operational definition of MBI and tested whether the presence of MBI was related to caregiver burden in patients with subjective cognitive decline (SCD) or MCI assessed at a memory clinic. Methods: MBI was assessed in 282 consecutive memory clinic patients with SCD ( n = 119) or MCI ( n = 163) in accordance with the International Society to Advance Alzheimer's Research and Treatment – Alzheimer's Association (ISTAART–AA) research diagnostic criteria. We operationalized a definition of MBI using the Neuropsychiatric Inventory Questionnaire (NPI-Q). Caregiver burden was assessed using the Zarit caregiver burden scale. Generalized linear regression was used to model the effect of MBI domains on caregiver burden. Results: While MBI was more prevalent in MCI (85.3%) than in SCD (76.5%), this difference was not statistically significant ( p = 0.06). Prevalence estimates across MBI domains were affective dysregulation (77.8%); impulse control (64.4%); decreased motivation (51.7%); social inappropriateness (27.8%); and abnormal perception or thought content (8.7%). Affective dysregulation ( p = 0.03) and decreased motivation ( p= 0.01) were more prevalent in MCI than SCD patients. Caregiver burden was 3.35 times higher when MBI was present after controlling for age, education, sex, and MCI ( p < 0.0001). Conclusions: MBI was common in memory clinic patients without dementia and was associated with greater caregiver burden. These data show that MBI is a common and clinically relevant syndrome.